Service Innovation Stimulus Inevitable For Marketing Performance of Retail Modern Trade in Thailand? Role of Service Innovation and Employee Engagement (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Marketing performance has become an essential factor for the organization’s success and gained the attention of researchers and regulators. Thus, the present research investigates the impact of services innovation and employee engagement on the organizational competencies and market performance of the Retail business in Thailand. This study also examines the mediating impact of organizational competencies among the relationships of services innovation, employee engagement and market performance of the Retail business in Thailand. This study has gathered the data from the retailers by using the questionnaires that were selected based on purposive sampling and used smart-PLS for analysis. The results indicated that services innovation and employee engagement have a positive association with organizational competencies and also with the market performance of the Retail business in Thailand. The outcomes also revealed that organizational competencies mediate among the links of services innovation, employee engagement and market performance of the Retail business in Thailand. This research is valuable for the regulators while developing regulations related to innovation adoption and market performance.